FEATURES OF TEACHER’S PERSONALITY DEVELOPMENT IN THE COURSE OF HIS PROFESSIONAL TRAINING - Natalia V. Akinina (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Currently, the process of teacher professional development is a continuous and controlled process, based on the creation of optimal organizational and pedagogical conditions necessary for the development and selfdevelopment of a foreign language teacher's personality. The problem of methodological literacy development among foreign language teachers, taking into account modern requirements for it, is the most urgent one, since the level of a teacher's professional competence depends on a foreign language teacher's methodology skill development, which subsequently develops into a system of methodological skills, as well as into a high level of student knowledge.